Community Empowerment through Capacity Building in the Hydroponic Revitalization and Crop Processing Program in Surabaya: Pemberdayaan Masyarakat melalui Capacity Building pada Program Revitalisasi Hidroponik dan Pengolahan Hasil Panen di Surabaya - Zico Ramdhani; Saka Palwaguna; Thufailah Nafiisah Bilqis; Reza Mehdi Fauzi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The initiation of community-based development requires innovative ideas from sustainable actors, such as university students, who serve as educated and productive agents of change. Through this approach, the KKN SDGs UPN “Veteran” Jawa Timur Period II, Group 16, aims to empower the community of RW 08, Pucang Sewu Subdistrict, using a comprehensive framework to ensure that the program is implemented with a clear structure and objectives. The program focuses on Sustainable Development Goals (SDGs) No. 8, Decent Work and Economic Growth, and No. 11, Sustainable Cities and Communities. These goals are selected due to their interconnection in promoting economic sustainability, community engagement, and environmental preservation for long-term well-being. The implementation of these principles is reflected in the community empowerment program through the revitalization of hydroponic systems for cultivating pakcoy and training on processing harvested crops. Pakcoy is chosen as the main commodity due to its relatively easy cultivation process and promising economic value. This initiative also encourages public awareness of food security and urban farming as a means of improving environmental management. The crop processing activity introduces pakcoy-based vegetable nuggets as an alternative healthy food source rich in fiber and low in allergens. The empowerment initiative is based on the capacity-building framework introduced by the United Nations Development Programme (UNDP) in 2017, which includes six pillars: stakeholder engagement, capability gap identification, goal setting, program formulation, capacity integration and progress analysis, and evaluation of community capability enhancement